Extraction, Characterisation and Antibacterial Activity of Caesalpinia bonducella Seed Oil Using n-Hexane as Solvent - Raman, N.; Muthumuniasamy, J. (Asian Journal of Chemistry, 2010)
The oil is extracted from Caesalpinia bonducella seeds using n-hexane as solvent. It is evaluated for oil content and some physicochemical characteristics. The oil shows antibacterial activity against the gram-negative bacteria Pseudomonas aerogenosa.